Lack of relationship between cellular density and either capillary density or metabolic rate in different regions of the brain - Baborie, Atik; Kuschinsky, Wolfgang (Neuroscience letters, 2006)
Whereas a pronounced correlation exists between local cerebral glucose utilization (LCGU) and capillary density in different regions of the brain, it is not known whether these parameters also correlate with the overall density of nuclei (cellularity). Therefore, cellularity was determined by diamidino-phenylindol (DAPI) fluorescent staining of nuclei in acetone-fixed frozen sections of the rat brain. A comparison of the density of nuclei in different brain regions showed much less variation than that observed in LCGU and capillary density. No correlation was found between nuclear density and either LCGU or capillary densities. In conclusion the cellular density is not a determinant of variation in LCGU and capillary density.
Gesehen am 30.04.2021